Enhancing student engagement with introductory microbiology and immunology topics using a novel board game - Rebecca S. Rivard (Journal of Microbiology & Biology Education)
ABSTRACT In introductory microbiology courses for non-biology majors, it can be difficult to ensure that students gain a functional understanding of the interplay between the host immune system and an invading infectious agent. Immune Battle is a board game that allows students to explore pathogen evolution and the immune system’s response to incursions in a captivating way, leveraging battleship and worker placement styles of gameplay. Students play in teams as either a pathogenic microbe attempting to reproduce and transmit itself to new hosts or as the immune system trying to defend the host from infection. Immune Battle seeks to mimic real-world interactions between immune cells and microbes using board game mechanics. For example, students will quickly find that adaptive immune system actions are better at fighting off microbial incursions than innate immune actions but require more time to activate. In this way, Immune Battle reinforces student’s understanding of the immune system and pathogenic virulence in an exciting and interactive way that keeps them thinking about host defenses long after the end of the class period or exam. This board game is well suited for advanced high school courses and introductory college-level courses that have only limited time to cover the immune system and microbiology. Documents containing the necessary components of the board game (not including a six-sided die) are included in the supplemental materials, so educators can print out their own copies and use this board game in their classes with no cost to themselves or their students.